1998
DOI: 10.1093/jn/128.9.1533
|View full text |Cite
|
Sign up to set email alerts
|

The Quantity of Dietary Protein Affects Brain Protein Synthesis Rate in Aged Rats

Abstract: The purpose of this study was to determine whether the quantity of dietary protein affects the rate of brain protein synthesis in aged rats. Experiments were conducted on three groups of 30-wk-old rats fed diets containing 0, 5 or 20 g casein/100 g for 10 d. The fractional rates of protein synthesis in brain, liver and kidney declined with a decrease in quantity of dietary protein. In brain, liver and kidney, RNA activity [g protein synthesized/(g RNA.d)] was significantly correlated with the fractional rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
0
28
1
Order By: Relevance
“…24) Direct evidence that the amino acid supply was important for neuronal protein synthesis was provided by the study of Parks et al 25) In previous studies, we found that the rate of protein synthesis in the brain declined with age, and decreased with the decrease in dietary protein in aged rats. 14,15) In older rats, we also reported that the rate of protein synthesis in the brain of rats given the gluten or gelatin diet is lower than in rats given the casein diet. 16) However, there is little information on the mechanism by which the dietary protein aŠects the protein synthesis rate in the brain in aged rats.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…24) Direct evidence that the amino acid supply was important for neuronal protein synthesis was provided by the study of Parks et al 25) In previous studies, we found that the rate of protein synthesis in the brain declined with age, and decreased with the decrease in dietary protein in aged rats. 14,15) In older rats, we also reported that the rate of protein synthesis in the brain of rats given the gluten or gelatin diet is lower than in rats given the casein diet. 16) However, there is little information on the mechanism by which the dietary protein aŠects the protein synthesis rate in the brain in aged rats.…”
Section: Discussionmentioning
confidence: 81%
“…[10][11][12][13][14] In older rats, we reported that the rate of protein synthesis in the brain depended on the quantity or quality of dietary protein consumed, and that a correlation between the rate of protein synthesis and the RNA concentration was not found in the brain when the dietary protein was manipulated. 15,16) However, little documentation for the mechanism by which the dietary protein alters the protein synthesis rate in the brain is available. Therefore, the purpose of our study was to discover whether the quantity and quality of dietary protein aŠects polysome proˆles in the brain of the aged rats.…”
mentioning
confidence: 99%
“…In weaned rats, a reduction with age in protein synthesis in the brain and skeletal muscle was related to a fall in RNA concentration (10,11). However, a positive correlation between the rate of protein synthesis and RNA activity was found in the brain of aged rats when the quantity and quality of dietary protein were manipulated (21,28). Hormonal treatment such as GH also appeared to elevate the rate of protein synthesis and RNA activity in the brain (14).…”
Section: Discussionmentioning
confidence: 99%
“…At 10 min after injection, rats were quickly decapitated. Specific radioactivities of [ 3 H]phenylalanine in tissue samples were determined according to the method described in our previous report ( 21 ). Tissue samples were homogenized with 10 volumes of cold 0.2 mol/L perchloric acid and then centrifuged at 2,800 ϫ g for 15 min at 4˚C.…”
Section: Methodsmentioning
confidence: 99%
“…At 10 min after injection, rats were quickly decapitated. Specific radioactivities of [ 3 H]phenylalanine in tissue samples were determined according to the method described in our previous report (20). In a preliminary experiment, we determined whether the method of Garlick et al (16) could be used to measure the rate of protein synthesis in the brain under this experimental condition.…”
Section: Methodsmentioning
confidence: 99%